Crisis Communication with Cognitive Radio Networks - Pravalika Gorremuchu,; Jagadishwari V,; Kesavamoorthy R,; Priyanka,; Mounica, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The disaster may occur naturally or may be due to human activities. As stated, precaution is better than cure predetermination of disaster also helps in management of communication lines but recovery after disaster plays a vital role which involves fixing the communication lines to allow necessary actions to be taken in the affected area. This survey analyses several methods that involve cognitive radio networks which help in transmission of signals. Several methods can be used to connect the transmission signals whereas on combining two different procedures of signal transmission like the UAVs and EC-CRVs which works on different protocols but when combined can help in increasing the overall efficiency of devices. More Precise outcome can be obtained in such manner.
Keywords: UAV; EC-CRV; Cognitive Radio Networks